2003
DOI: 10.1590/s0041-87812003000300002
|View full text |Cite
|
Sign up to set email alerts
|

Conventional approach x laparoscopic abdominoperineal resection for rectal cancer treatment after neoadjuvant chemoradiation: results of a prospective randomized trial

Abstract: OBJECTIVE:The aims of this study were to evaluate the safety and efficacy of laparoscopic abdominoperineal resection compared to conventional approach for surgical treatment of patients with distal rectal cancer presenting with incomplete response after chemoradiation.METHOD: Twenty eight patients with distal rectal adenocarcinoma were randomized to undergo surgical treatment by laparoscopic abdominoperineal resection or conventional approach and evaluated prospectively. Thirteen underwent laparoscopic abdomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
128
0
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(143 citation statements)
references
References 23 publications
5
128
0
10
Order By: Relevance
“…The operating time for LAC group was more, though statistically not significant, compared to the OR group (297 versus 180 minutes). This has been observed in other series as well [4,6,13,14]. A meta-analysis of the large randomized trials has shown a conversion rate of 19% [16].…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…The operating time for LAC group was more, though statistically not significant, compared to the OR group (297 versus 180 minutes). This has been observed in other series as well [4,6,13,14]. A meta-analysis of the large randomized trials has shown a conversion rate of 19% [16].…”
Section: Resultssupporting
confidence: 71%
“…Despite this, the better short term recovery of the LAC group could be demonstrated by the fewer days spent in the ICU and shorter hospital stay. This has been demonstrated in most of the other series as well [5,[10][11][12][13][14]16].…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Evidence comes mainly from several case series [4,[10][11][12], comparative nonrandomized studies [13][14][15], or randomized clinical trials (RCTs) [16][17][18][19][20][21] with a limited number of patients or a relatively short follow-up period.…”
Section: Discussionmentioning
confidence: 99%